Tinjauan Kelestarian Adat Perkawinan Suku Bada Di Desa Bewa Kecamatan Lore Selatan Kabupaten Poso - Alipa, Delviana; NUraedah (Jurusan Pendidikan IPS, Fakultas Keguruan dan Ilmu Pendidikan Universitas Tadulako, 2023)
This research aims to explain (1). Bada tribal wedding procession the decline in the traditional cultural value the role of traditional institutions in preserving traditional Bada tribal marriages in the village of Bewa. The subjects in this study were the role of traditional institutions and village government. The research method used is descriptive method with a quantitative approach. Data collection techniques are carried out through observation, interview and documentation. The results of this study indicate that the implementation of the Bada tribal marriages carried out in the village of Bewa until now is still carried out well, as one of the cultural heritages which contains values ​​that are very beneficial for the lives of generations of generations because they have very good meaning to do in married life and everyday life. Although experiencing a shift in value in the form of a dowry or a party slaughter that used to have to hold a buffalo in a party slaughter but now it can be replaced with cows, or cashed but does not change the cultural values ​​contained in the slaughter of the party and traditional clothes that used to have to use traditional clothes made from bark to use but now can use cloth Because it is rare that people make traditional clothes made of bark but do not reduce the value contained in these traditional clothes, the efforts of traditional institutions in preserving the bada tribal marriages in the village of Bewa are very good namely by socializing, providing understanding, applying and applying sanction.